2012
DOI: 10.1002/chem.201200430
|View full text |Cite
|
Sign up to set email alerts
|

The Gomberg–Bachmann Reaction for the Arylation of Anilines with Aryl Diazotates

Abstract: Simply aqueous sodium hydroxide is sufficient to exclude ionic side reactions and to prepare 2-aminobiphenyls from aryl diazotates and anilines through a new variant of the Gomberg-Bachmann reaction (see scheme). The metal-free reaction under basic conditions allows to exploit the highly radical-stabilizing effect of the aniline's free amino function for the first time, which leads to a so far unreached regioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 69 publications
6
37
0
Order By: Relevance
“…Pratsh et al [55] discussed the radical-mediated a-arylation anilines with aryl diazotates salt by easily accessible TMF conditions. The protocol scenario involved the reactions of anilines and aryl diazotates in the presence of NaOH/H 2 O to form corresponding o-arylated anilines 88 within the range of 43-68 % yields.The reaction conditions involved mild, simple and scalable conditions (Scheme 29).…”
Section: Arylation With Aryliodonium Saltmentioning
confidence: 99%
“…Pratsh et al [55] discussed the radical-mediated a-arylation anilines with aryl diazotates salt by easily accessible TMF conditions. The protocol scenario involved the reactions of anilines and aryl diazotates in the presence of NaOH/H 2 O to form corresponding o-arylated anilines 88 within the range of 43-68 % yields.The reaction conditions involved mild, simple and scalable conditions (Scheme 29).…”
Section: Arylation With Aryliodonium Saltmentioning
confidence: 99%
“…[19] After severalv ariations,aprocedure that provided aryldiazotate 2a as ac lear,a lmost colorless aqueous solution was established. [19] After severalv ariations,aprocedure that provided aryldiazotate 2a as ac lear,a lmost colorless aqueous solution was established.…”
Section: Resultsmentioning
confidence: 99%
“…[28] With the optimized conditions now available, we reevaluated the synthesis of as election of 2-aminobiphenyls 4.A comparison between the yields obtained from the previous protocol [19] and the newly developed procedure is summarized in Table 3. In less successful attempts, precipitate formation and the emergence of ay ellow color indicated the formation of undesired side products,s uch as diazo anhydrides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…118 In all cases, however, only small amounts of the desired 2-aminobiphenyls were isolated, and azo coupling and triazene formation were identified as the predominant pathways. We therefore concluded that diazo anhydrides [for example, 2,2′-oxybis(phenyldiazene)], which Rüchardt and Merz proposed as key intermediates in the Gomberg-Bachmann reaction, 119 are insufficiently protected forms of diazonium ions to suppress the ionic pathways.…”
Section: Scheme 31 Synthesis Of Biaryl 105 From 2-hydroxyphenyldiazonmentioning
confidence: 99%